Anime sebagai Media Pembelajaran Folklor Jepang - Nesa, Fakhria; Rahayu, Rachmidian (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
Using anime as a learning medium innovates Japanese language education, particularly in teaching Japanese folklore. This qualitative descriptive study assesses anime's efficacy in imparting knowledge of Japanese folklore to Japanese language learners. By examining various forms of folklore literature alongside anime featuring Japanese folklore themes, the research elucidates cultural meanings and societal aspects in Japan. For instance, "Kaguya Hime" anime adapts oral folklore, showcasing Japanese reverence for nature and Buddhist beliefs. "Chihayafuru" anime features Karuta, a traditional Japanese folk game, reflecting discipline and appreciation for nature depicted in Japanese poetry. "Deaimon" anime portrays non-verbal folklore through traditional Japanese cuisine, emphasizing Japan's reverence for nature evident in culinary artistry. The findings underscore anime's potential to deepen learners' understanding of Japanese culture and folklore, fostering cross-cultural appreciation and linguistic proficiency.